Calibration of the underground muon detector of the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Albury, J. M.; Allekotte, Ingomar; Almela, A.; Alvarez Muñiz, J.; Alves Batista, R.; Anastasi, G. A.; Anchordoqui, Luis A.; Andrada, B.; Andringa, S.; et al. (IOP Publishing, 2021)
Fil: Aab, A.. Radboud Universiteit Nijmegen; Países Bajos